Keefektifan Media Powtoon Dengan Pendekatan Problem Solving Untuk Meningkatkan Kemampuan Pemecahan Masalah Kelas III - Sulitiya Tri Ningsih; Lisa Virdinarti (Jurnal Perseda : Jurnal Pendidikan Guru Sekolah Dasar, 2021)
This study aims to determine the effectiveness of the use of powtoon media with a problem solving approach in improving the problem solving skills of the third grade students of SD N Sidomulyo 04. The problem faced is the students' low problem solving ability in the learning process. The type of research used is quantitative research. The data collection techniques used were observation, questionnaires, and tests. The population in this study were all class III SD in the East Ungaran sub-district, while the sample for this study was class III SD N Sidomulyo 04 East Ungaran. Data analysis techniques used normality test, homogeneity test, proportion test, comparative test, and regression test. The results obtained in this study are: (1) in the post-test of the experimental and control classes, the sig value of 0.111> 0.05 means that the students 'achievement of the students' problem-solving abilities is fulfilled, (2) Based on the independent sample T-Test output. The experimental and control classes show a sig value of 0.000 <0.05, which means that there is a significant difference between the experimental and control classes. (3) Based on the regression test output for the experimental and control classes, it shows that the pre-test, post-test and activeness values ​​show a sig value of 0.000 <0.05, which means that there is a significant effect on the activity of the experimental and control classes.